Icariside II Restores Vascular Smooth Muscle Cell Contractile Phenotype by Enhancing the Focal Adhesion Signaling Pathway in the Rat Vascular Remodeling Model - Lv, Junyuan; Li, Xintong; Wu, Hongyu; Li, Jiayang; Luan, Boyang; Li, Yiqi; Li, Yeli; Yang, Danli; Wen, Hao (Frontiers in Pharmacology, 2022)
Vascular smooth muscle cell (VSMC) phenotypic transition represented the fundamental pathophysiological alteration in the vascular remodeling process during the initiation and progression of cardiovascular diseases. Recent studies have revealed that Icariside II (ICS-II), a flavonol glycoside derived from traditional Chinese medicine Herba Epimedii, exhibited therapeutic effects in various cardiovascular diseases. However, the therapeutic efficacy and underlying mechanisms of ICS-II regarding VSMC phenotypic transition were unknown. In this study, we investigated the therapeutic effects of ICS-Ⅱ on vascular remodeling with a rats balloon injury model in vivo. Label-free proteomic analysis was further implemented to identify the differentially expressed proteins (DEPs) after ICS-II intervention. Gene ontology and pathway enrichment analysis were performed based on DEPs. Moreover, platelet-derived growth factor (PDGF-BB) induced primary rat VSMC was implemented to verify the restoration effects of ICS-II on VSMC contractile phenotype. Results showed that ICS-II could effectively attenuate the vascular remodeling process, promote SMA-α protein expression and inhibit OPN expression in vivo. Proteomic analysis identified 145 differentially expressed proteins after ICS-II intervention. Further bioinformatic analysis indicated focal adhesion signaling pathway was enriched in the ICS-II group. In vitro studies showed ICS-II suppressed VSMC proliferation and migration, and promoted VSMC contractile phenotype by modulating the focal adhesion signaling pathway. Taken together, our results suggest ICS-II attenuates the vascular remodeling process and restores VSMC contractile phenotype by promoting the focal adhesion pathway.